From a Multichannel to an Optichannel Strategy in Retail - Sílvia Faria; João M. S. Carvalho (Journal of Theoretical and Applied Electronic Commerce Research)
This paper presents the first systematic literature review (SLR) that includes the concept of an optichannel strategy, examining the main principles, key characteristics, and implications for retailers when switching from a multichannel to an optichannel approach. The SLR was made using Web of Science, Scopus, and Google Scholar to find literature on the optichannel model in retail. The results show a paradigm shift in retailing from a multichannel, passing through omnichannel and phygital, to an optichannel strategy. This shift means marketers are now adopting a more customer-centric approach to brand management and consumer behaviour. This article has practical and managerial implications for researchers and practitioners. For researchers, the study explains how retailers evolved from multi- to cross-, omni-, phygital, and optichannel strategies. For practitioners, this paper indicates future ways to allow retailers to manage their customers’ needs, ensuring a positive impact on customer experience and the company’s commercial and financial performance.